Comment les enfants justifient-ils ce qu'ils savent faire ? Le concept de milieu géométrique dans l'approche piagétienne de la formation des raisons - IOANNA BERTHOUD-PAPANDROPOULOU; HELGA KILCHER (Metaichmio Publications, 2008)
The relation between know-how and know to justify his/her action is explored within the Piagetian constructivist theoretical frame, particularly within the issue of Reasons. Reasons are considered as a reconstitution of the activity, contributing to its understanding by the subject. Thirty four children aged three to nine have been faced with a double task: determine the middle of geometric figures and then justify the chosen location. Results show that while determination is correctly performed at all ages by efficient perceptive evaluation, the justification undergoes a development leading from illustrative, to argumentative and finally to properly founding reasons from the age of eight years on. The relationship between action and reason is discussed on a cognitive, a social and an educational level.